2014
DOI: 10.1177/0969733014534877
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and legal challenges associated with disaster nursing

Abstract: In highlighting these issues, this article may provide a useful starting point for the development of an educational framework for preparing nurses and other health professionals to work in the disaster setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 10 publications
(10 reference statements)
0
66
0
4
Order By: Relevance
“…Previous studies have shown that during sudden natural disasters and infectious diseases, nurses risk their health to actively participate in the ght against the epidemic and provide assistance due to their moral and professional responsibility (35). They also could not refuse the hospital's request because they were aware of the shortage of staff and felt a serious responsibility as a nurse (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that during sudden natural disasters and infectious diseases, nurses risk their health to actively participate in the ght against the epidemic and provide assistance due to their moral and professional responsibility (35). They also could not refuse the hospital's request because they were aware of the shortage of staff and felt a serious responsibility as a nurse (21).…”
Section: Discussionmentioning
confidence: 99%
“…All nurses affirmed the importance of commitment and responsibility in their profession. They believed that disaster puts nurses in place beyond the normal scope of their activities [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Iran experiences significant disasters annually[ 14 , 15 ], there are limited studies in the field of disaster nursing that explore their problems[ 16 18 ]. Uncovering nurses’ experiences regarding disaster relief is important to inform future relief efforts and the development of programs to enable nurses participate with some confidence in future events[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10] In addition, the knowledge related to earthquake disasters from the literature review [5][6][7][19][20][21] was added in the framework. Based on the ICN disaster nursing competencies framework, knowledge on the response and recovery phases is the most important for nurses in the hospital setting.…”
Section: Literature Reviewmentioning
confidence: 99%